(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the field of onomastics—the study of names and naming practices—as a vital component of linguistic and cultural identity. Through the analysis of personal names, place names, and literary onomastics, the article highlights how names function not only as identifiers but also as carriers of historical, social, and cultural meaning. Drawing from examples in different languages and cultures, the study illustrates the interdisciplinary relevance of onomastics in sociolinguistics, anthropology, literature, and history. Emphasis is placed on how names reflect collective memory, social structures, and cultural values. The article concludes that onomastic research offers crucial insights into the identity and worldview of a community, serving as a powerful tool in understanding both linguistic evolution and cultural continuity.